Eco-Friendly Design of Chitosan-Based Films with Biodegradable Properties as an Alternative to Low-Density Polyethylene Packaging - Garcia-Herrera, C; Inostroza-Inostroza, M (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Biopolymer-based films are a promising alternative for the food packaging industry, in which petrochemical-based polymers like low-density polyethylene (LDPE) are commanding attention because of their high pollution levels. In this research, a biopolymer-based film made of chitosan (CS), gelatin (GEL), and glycerol (GLY) was designed. A Response Surface Methodology (RSM) analysis was performed to determine the chitosan, gelatin, and glycerol content that improved the mechanical properties selected as response variables (thickness, tensile strength (TS), and elongation at break (EAB). The content of CS (1.1% w/v), GEL (1.1% w/v), and GLY (0.4% w/v) in the film-forming solution guarantees an optimized film (OPT-F) with a 0.046 ± 0.003 mm thickness, 11.48 ± 1.42 mPa TS, and 2.6 ± 0.3% EAB. The OPT-F was characterized in terms of thermal, optical, and biodegradability properties compared to LDPE films. Thermogravimetric analysis (TGA) revealed that the OPT-F was thermally stable at temperatures below 300 °C, which is relevant to thermal processes in the food industry of packaging. The reduced water solubility (WS) (24.34 ± 2.47%) and the improved biodegradability properties (7.1%) compared with LDPE suggests that the biopolymer-based film obtained has potential applications in the food industry as a novel packaging material and can serve as a basis for the design of bioactive packaging. © 2024 by the authors.